CLINICAL SPECTRUM AND RISK FACTORS INFLUENCING PEDIATRIC MALARIA PUBLIC HEALTH CONCERN IN DISTRICT LOWER DIR (Journal of Medical & Health Sciences Review, 2025)
Malaria poses a major health crisis in District Dir Lower, Khyber Pakhtunkhwa, Pakistan, disproportionately affecting children as a vulnerable population in the region. The annual prevalence of malaria among children stands at 81.35%. Monthly prevalence rates fluctuate, peaking in May (85.71%), June (84.44%), and July (86.00%), likely due to favourable environmental conditions such as higher humidity and the rainy season, which increase mosquito breeding. Conversely, the lowest prevalence is observed in March (68.57%) and December (75.76%). Gender-wise analysis indicates that male children have a higher prevalence rate of 84.09% compared to female children at 78.42%. Age-wise data reveals that children aged 9-10 years have the highest prevalence at 83.69%, followed by those aged 1-4 and 5-8 years, each exhibiting a prevalence rate of 80.00%. Plasmodium vivax was the most prevalent species, accounting for 75.79% of the total positive cases, followed by Plasmodium falciparum at 15.08% and mixed infections at 3.94%. Seasonal variations show a higher prevalence during the summer months (83.03%) compared to winter (78.76%), aligning with increased mosquito activity in warmer temperatures. Tehsil-wise data indicates that Timergara has the highest prevalence at 15.2%, while Samar Bagh has the lowest at 9.6%. These findings underscore the need for targeted malaria control strategies, particularly during peak transmission periods and in areas with higher prevalence rates.